Migrace za prací a trh práce (na příkladu Královehradeckého kraje) - Netušilová, Radka (Univerzita Pardubice, 2006)
Práce se věnuje migraci za prací v okrese Trutnov. Zabývá se zhodnocením prostorové mobility pracovních sil v okrese Trutnov z hlediska vymezení zdrojů, směru, intenzity pohybu za prací a sledování závislosti podílu dojíždějících na vzdálenosti bydliště-pracoviště.

This thesis attends to a labour migration in Trutnov Region. The Thesis consists of four parts. In the first part, basic terms relating to spatial mobility used in the labour migration terminology are explained. The second part gives an outline of theoretical approaches to regional labour markets, and determines not only the basic terms but also theoretical associations with regional labour markets functioning. The third part describes factors influencing professional and territorial labour mobility on the part of job offers and inquiries. The last part is concerned with the evaluation of spatial labour mobility in Trutnov Region as to the determination of human resources, direction and intensity of job migration and the monitoring of the dependency rate of commuters in the „place of residence – workplace‘‘ distance
Labour migration and labour market of Hradec Králové region
Keywords: labour migration; regional labour market; spatial labour mobility; Migrace; prostorová mobilita; Trh práce; pracovní mikroregiony